Contribution of proteomics for diving into the lactic acid bacteria role and the modification of the food matrix during fermentation - Fadda, Silvina G. (2012)
Fermentation and drying can be considered as the oldest ways to preserve raw materials extending the shelf-life as well as enhancing the flavour and nutritional qualities of the products. Lactic acid bacteria (LAB) are the main agents responsible for fermentation, reducing the ripening time, minimizing manufacturing defects, improving sensory properties and inhibiting the development of pathogenic and spoilage flora. LAB is also considered as the most important microorganism responsible for the health-promoting effects of fermented foods, especially in milk-derived products. Indeed, strains of some species have traditionally been used as probiotics and added as functional bacteria in various food commodities [1]. Due to the huge economic significance of industrial application of LAB as starters, biopreservatives and probiotics, a research emphasis on their metabolism, genetic and applications has been placed in the last 25 years [2].